Template directed incorporation of nucleotide mixtures using azole-nucleobase analogs. - Hoops, G C (1997)
DNA that encodes elements for degenerate replication events by use of artificial nucleobases offers a versatile approach to manipulating sequences for applications in biotechnology. We have designed a family of artificial nucleobases that are capable of assuming multiple hydrogen bonding orientations through internal bond rotations to provide a means for degenerate molecular recognition. Incorporation of these analogs into a single position of a PCR primer allowed for analysis of their template effects on DNA amplification catalyzed by Thermus aquaticus (Taq) DNA polymerase. All of the nucleobase surrogates have similar shapes but differ by structural alterations that influence their electronic character. These subtle distinctions were able to influence the Taq DNA polymerase dependent incorporation of the four natural deoxyribonucleotides and thus, significantly expand the molecular design possibilities for biochemically functional nucleic acid analogs.